Resveratrol activates CD8+ T cells through IL-18 bystander activation in lung adenocarcinoma - Zhang, Wei; Zhang, Ruohao; Chang, Zhiguang; Wang, Xiaobo (Frontiers in Pharmacology, 2022)
Resveratrol, a natural product, has demonstrated anti-tumor effects in various kinds of tumor types, including colon, breast, and pancreatic cancers. Most research has focused on the inhibitory effects of resveratrol on tumor cells themselves rather than resveratrol’s effects on tumor immunology. In this study, we found that resveratrol inhibited the growth of lung adenocarcinoma in a subcutaneous tumor model by using the β-cyclodextrin-resveratrol inclusion complex. After resveratrol treatment, the proportion of M2-like tumor-associated macrophages (TAMs) was reduced and tumor-infiltrating CD8T cells showed significantly increased activation. The results of co-culture and antibody neutralization experiments suggested that macrophage-derived IL-18 may be a key cytokine in the resveratrol anti-tumor effect of CD8T cell activation. The results of this study demonstrate a novel view of the mechanisms of resveratrol tumor suppression. This natural product could reprogram TAMs and CD8T effector cells for tumor treatment.